2010
DOI: 10.1108/07378831011096196
|View full text |Cite
|
Sign up to set email alerts
|

Artificially intelligent conversational agents in libraries

Abstract: PurposeConversational agents are natural language interaction interfaces designed to simulate conversation with a real person. This paper seeks to investigate current development and applications of these systems worldwide, while focusing on their availability in Canadian libraries. It aims to argue that it is both timely and conceivable for Canadian libraries to consider adopting conversational agents to enhance – not replace – face‐to‐face human interaction. Potential users include library web site tour guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 23 publications
1
52
0
Order By: Relevance
“…In our KO curricula, I argue, increased prominence should be given to the appreciation and research into language, its use, structure, and its automated analyses. Looking beyond both the 19th and 20th century paradigms, libraries are likely to consider incorporating more language technologies beyond now standard search capabilities, such as conversational agents (Rubin, Thorimbert, and Chen, 2010 Dr. Pattuelli will discuss the results of a recent investigation she conducted on the current state of knowledge organization education in ALA-accredited schools of library and information science. The study examined the subject content of knowledge organization courses taught in 57 ALA-accredited LIS programs and was based on a pilot study conducted on the ten top-ranked ten LIS schools.…”
Section: Teaching Linked Data and The Semantic Web To Mlis Studentsmentioning
confidence: 98%
“…In our KO curricula, I argue, increased prominence should be given to the appreciation and research into language, its use, structure, and its automated analyses. Looking beyond both the 19th and 20th century paradigms, libraries are likely to consider incorporating more language technologies beyond now standard search capabilities, such as conversational agents (Rubin, Thorimbert, and Chen, 2010 Dr. Pattuelli will discuss the results of a recent investigation she conducted on the current state of knowledge organization education in ALA-accredited schools of library and information science. The study examined the subject content of knowledge organization courses taught in 57 ALA-accredited LIS programs and was based on a pilot study conducted on the ten top-ranked ten LIS schools.…”
Section: Teaching Linked Data and The Semantic Web To Mlis Studentsmentioning
confidence: 98%
“…Other general applications of virtual assistants are in the area of education for instructions and learning [8], delivering information from large data sets like encyclopedias in libraries [9], for informational purposes in e-commerce [10], merging heterogeneous data using multi-agent conversational agents [11], tourism [12], and several others.…”
Section: Related Workmentioning
confidence: 99%
“…Authors have posited ways ECAs (also called avatars) might be used in libraries (Balleste, 2007;Rubin et al, 2010). Despite this theoretical interest, reviews of the relevant library literature by Rubin et al (2010) and Liu (2011) found that implementation is rare. One exception, identified by Liu, is Neva, an embodied conversational agent available on kiosks in the McLuhan Documentation Center at the University of Lubeck.…”
Section: Animation In Librariesmentioning
confidence: 99%